Analisis Kontrastif Kalimat Pasif Bahasa Indonesia dengan Bahasa Inggris - Djuria Suprato (Bina Nusantara University, 2012)
The difficulty of a teacher to teach a second language to students can be addressed by contrastive analysis, where it is assumed that learning a second language is influenced by the first language acquisition. The purpose of this article is to describe the level of a comparable degree of passive sentences in Indonesian and English to provide benefits as a reference in the teaching of English as a second language. This study was conducted with qualitative methods, the reference library of resources Indonesian and English. Passive Sentences in Indonesian views of the structure using the